The pathogenesis-related protein 1 (PR-1) gene in rice (Oryza sativa): isolation, sequencing and bioinformatics analysis - Beyazyuz, Fadime; Filiz, Ertugrul (Acta Biologica Szegediensis, 2026)
Pathogenesis-related 1 (PR1) proteins constitute an important gene family that participates in plant responses to both biotic and abiotic stresses. The aim of this study was to isolate and sequence a PR1 gene from rice (Oryza sativa) and to characterize the encoded protein using bioinformatics tools. Sequencing revealed a 441-bp exon encoding a 147-amino-acid protein. OsPR1 contained a PF00188 cysteine-rich secretory protein (CAP) domain and a 21-amino-acid signal peptide. Phylogenetic analysis indicated that OsPR1 is clustered with PR1 proteins from Sorghum bicolor and Zea mays within the monocot clade. Protein–protein interaction predictions suggested putative functional associations of OsPR1 with enzymes involved in nitrogen and purine metabolism. Structural modeling and comparison with Arabidopsis thaliana PR1 (AtPR1) revealed a high degree of three-dimensional conservation. These data provide experimental confirmation of a rice PR1 gene and offer a framework for future functional studies on PR1-mediated stress responses in rice.